Contents tourism and pop culture fandom transnational tourist experiences - Yamamura, Takayoshi 1971-; Seaton, Philip A. 1972- (Aspects of tourism, 2020)
This is the first book to apply the concept of ‘contents tourism’ in a global context and to establish an international and interdisciplinary framework for contents tourism research. The term ‘contents tourism’ gained official recognition in Japan when it was defined by the Japanese government in 2005, and it has been characterised as ‘travel behaviour motivated fully or partially by narratives, characters, locations, and other creative elements of popular culture forms including film, television dramas, manga, anime, novels and computer games’. The book builds on previous research from Japan and explores three main themes of contents tourism: ‘the Contentsization of Literary Worlds’, ‘Tourist Behaviours at "Sacred Sites" of Contents Tourism’ and ‘Contents Tourism as Pilgrimage’ and draws together these key themes to propose a set of policy implications for achieving successful and sustainable contents tourism in the 21st century